Strategy for Utilizing Duolingo as an Interactive Learning Media to Improve Vocational High School Students' Oral Communication Skills - Kurniati, Erisa; Kumalasari, Ade; Mukhoiyaroh, Siti Enik; Waldo, Kevin; Akbar, Risky; Suhardi, Suhardi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study investigates the strategic use of Duolingo as an interactive learning medium to enhance oral communication skills among vocational high school students. Employing a mixed-methods convergent parallel design, data were collected from 30 students and two English teachers through pre- and post-speaking tests, motivation and engagement questionnaires, classroom observations, and semi-structured interviews. The data were analyzed using complementary quantitative and qualitative techniques. The quantitative results demonstrated significant improvements across all speaking dimensions, with the most tremendous gains in communicative competence (M gain = +1.6). The questionnaire findings revealed high levels of motivation and engagement, driven by Duolingo's gamification features, although self-regulation remained a challenge. Qualitative data confirmed that students developed greater confidence and improved vocabulary retention, while teachers emphasized the benefits of integrating Duolingo with communicative tasks, such as role-playing and group discussions. Classroom observations further indicated progressive increases in participation, vocabulary use, and enthusiasm throughout the intervention. These findings suggest that Duolingo is most effective when strategically embedded within interactive classroom practices, aligning with the Merdeka Belajar curriculum by fostering learner autonomy, motivation, and communicative competence. This research offers a novel contribution by demonstrating that, despite these challenges, the effectiveness of technology-enhanced learning ultimately hinges on the overlooked yet critical roles of teacher mediation and institutional support.